Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(A=\left(x^2-2x\right)\left(x^2-2x-1\right)-6=\left(x^2-2x\right)^2-\left(x^2-2x\right)-6\)
\(=\left(x^2-2x+2\right)\left(x^2-2x+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(viết lại đề nha)
<=>(2ab-a2-b2+1)(2ab+a2+b2-1)=[-(a-b)2+1][(a+b)2-1]=(1-a+b)(1+a-b)(a+b-1)(a+b+1)
b)
<=>(xy+4-2x-2y)(xy+4+2x+2y)
c)
<=>(x2-3)(x2+3)+2x(x2+3)=(x2+3)(x2-3+2x)=(x2+3)[(x+1)2-4]=(x2+3)(x+1-2)(x+1+2)=(x2+3)(x-1)(x+3)